Set-Valued Hardy-Rogers Type Contraction in 0-Complete Partial Metric Spaces. (7th April 2014) - Shukla, Satish; Radenović, Stojan; Vetro, Calogero
Abstract : In this paper we introduce set-valued Hardy-Rogers type contraction in 0-complete partial metric spaces and prove the corresponding theorem of fixed point. Our results generalize, extend, and unify several known results, in particular the recent Nadler's fixed point theorem in the context of complete partial metric spaces established by Aydi et al. (2012). As an application of our results, a homotopy theorem for such mappings is derived. Also, some examples are included which show that our generalization is proper.